(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Both China and India have a lengthy history of public health education that is both deeply attentive to each country’s unique needs and medical traditions, as well as sensitive to global influences. Throughout the Republican Era in China, American and European organizations made substantial contributions to public health education (1911-1949). Prior to India’s independence in 1947, the British Empire had an influence on the country’s centuries-old health-care traditions. Political unrest in both countries throughout the 1940s had an impact on public health systems and public health education. The major goal of this research is to provide a broad review of public health education in India and Mainland China, with a focus on historical organizations and structures that have contributed in the establishment of organized public health education. We examine the current issues to identify where we can make changes. Health reforms in China and India must investigate innovative and modern models for public health education, maybe in independent faculties of public health, to revive public health education and strengthen the role of public health in addressing the health concerns of the twenty-first century.